HUBUNGAN PROPORSI VENTILASI BERDASARKAN VOLUME RUANGAN DAN ORIENTASI MATAHARI DENGAN TUBERKULOSIS PARU DI PUSKESMAS MRANGGEN II KABUPATEN DEMAK - Istiqomah Istiqomah; Mursid Rahardjo; Nurjazuli Nurjazuli (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Background: Pulmonary tuberculosis (TB) is a disease that can be transmitted by patients when coughing from sputum splash containing Mycobacterium tuberculosis. In 2016 Mranggen II Health Center was ranked third with the number of TB patients from 27 health centers in Demak Regency, namely 36 cases with a new case finding rate of 52.48 per 100,000 population. The purpose of this study was to analyze the relationship between the proportion of ventilation based on room volume and the orientation of sunlight into the house with the incidence of pulmonary tuberculosis in the region of Mranggen II Public Health Center in Demak Regency. Method: Observational study with case control design. The sample used was 70 respondents consisting of 35 cases and 35 controls. Analysis data using chi-square. Results: The results of bivariate analysis showed a significant relationship and a risk factor for the incidence of pulmonary TB, that was the proportion of ventilation based on room volume (p-value = 0.001, OR = 6.250 with 95% CI = 2.215 - 17.632), and the orientation of sunlight into the house (p-value = 0,0001, OR = 36,000 with 95% CI = 7,299 - 177,553). Conclusion: The proportion of ventilation based on room volume and the orientation of sunlight into the house including risk factors for the incidence of pulmonary tuberculosis in Mranggen II Public Health Center in Demak Regency.